Reversible strain-induced spin-orbit torque on flexible substrate - Wong, Grayson Dao Hwee (2021)
We propose the use of mechanical strain and mild annealing to achieve reversible modulation of spin-orbit torque (SOT) and Gilbert damping parameter. X-ray diffraction results show that the residual spin-orbit torque enhancement and Gilbert damping reduction, due to the post-mechanical strain treatment, can be reset using mild annealing to alleviate the internal strain. The spin Hall efficiency of the heat- and strain-treated Pt/Co bilayer was characterized through spin-torque ferromagnetic resonance, and it was found that the device could switch between the strain enhanced SOT and the pristine state. The Gilbert damping parameter behaves inversely with the spin Hall efficiency, and therefore, strain can be used to easily tune the device switching current density by a factor of ∼2 from its pristine state. Furthermore, the resonance frequency of the Pt/Co bilayer could be tuned using purely mechanical strain, and from the endurance test, the Pt/Co device can be reversibly manipulated over 104 cycles demonstrating its robustness as a flexible device.